2020
DOI: 10.48550/arxiv.2012.10640
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hosts and triggers of AGNs in the Local Universe

Ziwen Zhang,
Huiyuan Wang,
Wentao Luo
et al.

Abstract: Based on the spectroscopic and shear catalogs for SDSS galaxies in the local Universe, we compare optically-selected active galactic nuclei (AGNs) with control star-forming and quiescent galaxies on galactic, inter-halo and larger scales. We find that AGNs are preferentially found in two specific stages of galaxy evolution: star-burst and 'green valley' phases, and that the stellar population of their host galaxies is quite independent of stellar mass, different from normal galaxies. Combining galaxy-galaxy le… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 100 publications
(145 reference statements)
2
3
0
Order By: Relevance
“…Based on our modeling procedure (Section 4), the AGNs typically reside in halos with a characteristic mass of log(M h /h −1 M ) = 12.22 (Table 2). This halo mass is close to other published studies where our value is about 0.3dex lower than X-ray detected AGN (Leauthaud et al 2015), and 0.3 dex higher than the SDSS opticallyselected AGNs (Mandelbaum et al 2005;Zhang et al 2020).…”
Section: Halo Mass Profile Modellingsupporting
confidence: 91%
“…Based on our modeling procedure (Section 4), the AGNs typically reside in halos with a characteristic mass of log(M h /h −1 M ) = 12.22 (Table 2). This halo mass is close to other published studies where our value is about 0.3dex lower than X-ray detected AGN (Leauthaud et al 2015), and 0.3 dex higher than the SDSS opticallyselected AGNs (Mandelbaum et al 2005;Zhang et al 2020).…”
Section: Halo Mass Profile Modellingsupporting
confidence: 91%
“…Additionally, the same model is in better agreement with observationally inferred P AGN distributions. This model also assumes: (i) a stellar mass -halo mass relation as derived in Grylls et al (2019), which reproduces the most recent estimates of the local galaxy stellar mass function by Bernardi et al (2017), and it is consistent, as shown in Figure 7, with the large-scale clustering of local central AGN in SDSS (Zhang et al 2020), and SDSS galaxies with photometry from Domínguez Sánchez et al (2018); (ii) A parameter Q ≤ 2 as suggested by observations of the AGN satellite fraction at low redshifts (e.g. Allevato et al 2012;Leauthaud et al 2015).…”
Section: Bias Vs M Star /M Bhsupporting
confidence: 64%
“…Present data do not allow us to clearly distinguish between models with and without a covariant scatter. In fact, as shown in Figure 7 (left panel), currently available AGN bias estimates as a function of stellar mass of SDSS AGN (Zhang et al 2020) only extend up to M star ∼ 10 11.3 M , where the models have just started to diverge (solid gray versus long dashed green lines), although the data tend to be closer to the model without covariant scatter. AGN clustering measurement at higher host galaxy stellar mass bins will become available in the near future (e.g., Euclid) allowing us to rule out, or confirm, a covariant scatter at a high confidence level.…”
Section: Additional Dependencies In the Inputmentioning
confidence: 91%
See 2 more Smart Citations